Eficiência técnica da saúde no estado do Ceará: uma análise empírica das taxas de mortalidades dos municípios cearenses no ano de 2022 - Rodrigues, Francisco Bruno Martins (2024)
The present study aims to measure the efficiency of healthcare spending in the municipalities of Ceará, Brazil. Over the decades, healthcare has emerged as a persistent bottleneck in public policies, with challenges ranging from unequal resource distribution to the need for innovative strategies to address the growing demands of society. Thus, an analysis is justified to measure the most efficient municipalities and establish parameters for the most successful policies. To establish this metric, the stochastic frontier model was employed. This type of model describes the maximum output (production) that can be obtained with each feasible combination of inputs (inputs such as labor, capital, machinery, among others), constrained by technology. It parametrically describes the threshold or production frontier. A database was assembled for model formulation, incorporating data from various sources such as IBGE (Brazilian Institute of Geography and Statistics), SUS (Unified Health System), and the Transparency Portal. Based on these data, the models were then executed to measure the efficiency of municipalities and enable their comparison.